Association between HLA-Ⅱgene polymorphism and Helicobacter pylori infection in Asian and European population: A meta-analysis. (May 2015) - Wang, Jingqiu; Zhang, Qun; Liu, Yali; Han, Jian; Ma, Xingming; Luo, Yanping; Liang, Yaling; Zhang, Lifeng; Hu, Yonghao
Abstract: Background: It is generally considered that HLA-Ⅱ genes contribute to the Helicobacter pylori ( Hp ) infection and disease development process. Aims: To perform a meta-analysis to explore the relationship between HLA-Ⅱgene polymorphism and host susceptibility to Hp infection. Methods: Relevant cohort studies, case-control studies and cross-sectional studies were identified by searching Cochrane Library, PubMed, EMBASE, Web of Science and CBM up to July 2014. The data were extracted and methodological quality of the studies were evaluated. RevMan5.0 software was used to perform statistical analysis. Results: In Asian population, HLA-DQB1∗0303 acted as the protective gene in Hp infection (statistically significant pooled OR = 0.54) and the susceptible genes in Hp infection involved HLA-DQB1∗0401, HLA-DQA1∗0103 and HLA-DQA1∗0301 (statistically significant pooled OR and 95%CI were 3.34(1.93, 5.77), 1.64(1.16, 2.33) and 2.03(1.20, 3.44) respectively). No statistically significant difference between DQB1∗0303, HLA-DQA1∗0103 and DQA1∗0301 and Hp infection in European population ( P >0.05). And no statistically significant difference ( P >0.05) in the overall effect of the association between the rest of HLA-Ⅱalleles and Hp infection. Conclusions: In Asian population, the protective gene HLA-DQB1∗0303 and the susceptible genes HLA-DQB1∗0401, HLA-DQA1∗0103 and HLA-DQA1∗0301 in Hp infection were established by meta-analysis. And there was no HLA-Ⅱallele was found to associate with Hp infection among European population. Highlights: Meta-analysis was performed on the relationship between HLA-Ⅱalleles and Hp infection. Asian and European population were included respectively in the subgroup analysis. Some HLA-Ⅱalleles are associated with Hp infection in Asian population. Ethnicity may be an important factor that affects the susceptibility to Hp . The meta-analysis is necessary.